Shaken, Not Stirred! James Bond in the Spotlight of Physics - Tolan, Metin; Stolze, Joachim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
How do James Bond's X-ray glasses work, the ones he uses to see whether the lady at the roulette table has a pistol concealed in her underwear? Is it really possible to launch oneself into the air and catch up with a plane that is free-falling towards the earth? Or to shoot down a helicopter with a pistol? In this lively and informative book, Germany's boldest physics professor Metin Tolan analyses the stunts and gadgets of the 007 films and even answers the question of all questions: Why does Bond drink his vodka martini shaken, not stirred? "So much entertaining science is a rare thing." Spiegel Online.
A quantum of physics -- The Daniel Craig Bond movies -- Myths and facts from Goldfinger -- The physics in Moonraker -- Unbelievable chases -- Gimmicks & gadgets -- "Shaken, not stirred!" -- How this Book Came About.
Keywords: Physics; Mechanics; Mechanics, Applied; Motion pictures-History.; Electrical engineering; Popular Science in Physics; Theoretical and Applied Mechanics; Film History; Electrical Engineering